2014
DOI: 10.2478/pjct-2014-0076
|View full text |Cite
|
Sign up to set email alerts
|

Impact of heating rate and solvent on Ni-based catalysts prepared by solution combustion method for syngas methanation

Abstract: Ni-Al 2 O 3 catalysts prepared by solution combustion method for syngas methanation were enhanced by employing various heating rate and different solvent. The catalytic properties were tested in syngas methanation. The result indicates that both of heating rate and solvent remarkably affect Ni particle size, which is a key factor to the catalytic activity of Ni-Al 2 O 3 catalysts for syngas methanation. Moreover, the relationship between Ni particle size and the production rate of methane per unit mass was cor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…The second peak could be assigned to β-type NiO species with medium interaction with the catalyst support. Meanwhile, the high-temperature peak is assigned to γ-type NiO species which are NiO particles with strong interaction with the support and the stable nickel aluminate phase with the spinel structure (NiAl 2 O 4 ). , …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The second peak could be assigned to β-type NiO species with medium interaction with the catalyst support. Meanwhile, the high-temperature peak is assigned to γ-type NiO species which are NiO particles with strong interaction with the support and the stable nickel aluminate phase with the spinel structure (NiAl 2 O 4 ). , …”
Section: Resultsmentioning
confidence: 99%
“…Meanwhile, the hightemperature peak is assigned to γ-type NiO species which are NiO particles with strong interaction with the support and the stable nickel aluminate phase with the spinel structure (NiAl 2 O 4 ). 84,85 It was found that all of the as-prepared catalysts 30Ni/ MTK_C, 30Ni/MTK_M, 30Ni−20Ce/MTK_C, and 30Ni− 20Ce/MTK_M contained three types of NiO species, which are α, β, and γ types. Considering the highest reduction peak (β type) of the 30Ni/MTK_M catalyst, the peak was shifted to a lower temperature.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, it can improve the active components of the catalysts owing to its characteristics, thus promoting the reforming of hydrogen. Zeng et al [31] studied the effects of Mg, Mn, and La additives on the catalytic performance of Ni-based reforming. They found that the catalysts containing La exhibited smaller Ni particles and better CO adsorption performance after reduction.…”
Section: Particle Size Distribution and Reducibilitymentioning
confidence: 99%
“…As we all know, the properties of the supported catalyst are greatly determined by the feature of the support. The catalytic support can also greatly impact a lot of characteristics of the catalyst, for instance, the metal–support interaction, acid–base property, redox property, and so forth. Therefore, a lot of newly designed porous materials, such as mesoporous silicates, mesoporous metal oxides, metal–organic frameworks, zeolitic imidazolate frameworks, and so forth are extensively employed as the supports of Ni-based CO 2 methanation catalysts.…”
Section: Introductionmentioning
confidence: 99%